Education and Assistance to Residents Regarding Organic Waste Processing Using the Ecoenzyme Method - Surani, Vincencius; Pranata, Lilik; Hardika, Bangun Dwi; Daeli, Novita Elisabeth; Suryani, Ketut; Rini, Maria Tarisia; Aprezia, Tezi Kharina; Sari, Lezi Mayang; Indaryati, Sri; Ajul, Keristina (PT. Riset Press International, 2025)
The increase in population in Indonesia means that the amount of food consumption also increases, if not accompanied by good environmental problems, will have a major impact, especially the problem of waste produced by the community, one of which is organic waste consisting of vegetables, fruits, and others; therefore there must be useful activities in managing the waste. The purpose of community service activities is to increase public knowledge about the processing of organic waste into coenzymes. The method educates and simulates exoenzymes made from vegetables processed from household waste. Participants in the activity were 15 people gathered in one place; the activity was carried out on May 15, 2024. The activity process began with planning, activities, and evaluation. The activity results showed that the participants were enthusiastic and very interested in participating in this education; there was an increase in public knowledge about managing organic waste into coenzymes. The conclusion of the activity shows that the community must often be given education and direct assistance to improve its ability, one of which is the processing of household waste in the form of vegetables, fruits, and other things.